Perfil epidemiológico dos transtornos psiquiátricos de criançãs e adolescentes internados em hospital de referência - Vargas, Ciro Mendes (2014)
Information about pediatric and adolescent patients admitted to specialized psychiatric hospitals are rare and there are few data on the epidemiological profile of these patients. Two studies were conducted in order to investigate this population. Aiming to review the literature concerning this issue, the first study found 17 relevant articles that indicated conduct disorder and affective disorders as most prevalent diagnostics among the studies. There was gender balance. There was no ethnic differences. In the second study, were analyzed medical charts of 1318 patients under 18 years old admitted from January 2001 to December 2011 at a referral hospital in child psychiatric hospitalization. The most frequent diagnosis was Bipolar Disorder (35.4%). There was a significant male majority in bipolar disorder, organic mental disorder and substance-related disorder, female majority in depressive disorder and dissociative disorder. Prevalence of bipolar and related substance in the range 15-18 years and prevalence of organic mental disorder and attention-deficit hyperactivity disorder in the range of 10 to 14 years. Psychiatric family history occurred in greater frequency in the range 10-18 years. Comorbidities were present in 46.2% of the sample. The psychotic syndrome was the most frequent described. In an overview of the two studies, externalizing disorders were more common in younger children and males, and internalizing disorders in older children and females.